Possibilities of echocardiographic screening in athletes. Part 1. Normal values - A. S. Sharykin; V. A. Badtieva; Iu. M. Ivanova; D. M. Usmanov (National Electronic Information Consortium (NEICON), 2023)
Objective: assess the suitability of existing domestic and international recommendations for the use of echocardiography as a screening method for examining athletes; to select standards that characterize the heart in different sports, based on their own research.Materials and methods: a meta‑analysis of 38 domestic and foreign literature sources based on the results of an echocardiographic examination of athletes was carried out. The indicators of 2647 male athletes aged 16 to 45 years old, playing for the national teams of the city of Moscow and having passed an in‑depth medical examination at the Sports Medicine Clinic, were studied.Results: heart sizes in athletes differ slightly from population indicators, however, in 14-45% of cases they go beyond the reference values. In the absence of heart disease, the largest dimensions of the left ventricle (LV) are observed in endurance exercisers. At the same time, high functionality correlates with increased LV volume indexed by BCA (for EDV/BSA and VO2 AT r = 0.52, p < 0.05).Conclusion: echocardiographic screening of athletes allows obtaining sufficient information to identify congenital or pathology that has arisen during excessive training loads. As standards, it is advisable to use population indicators expressed in centile values.